Bioelectricity Production and Comparative Evaluation of Electrode Materials in Microbial Fuel Cells Using Indigenous Anode-Reducing Bacterial Community from Wastewater of Rice-Based Industries - Shailesh Kumar Jadhav; Reena Meshram (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Microbial fuel cells (MFCs) are the electrochemical systems that harness the electricity production capacity of certain microbes from the reduction of biodegradable compounds. The present study aimed to develop mediator-less MFC without using expensive proton exchange membrane. In the present study, a triplicate of dual-chamber, mediator-less MFCs was operated with two local rice based industrial wastewater to explore the potential of this wastewater as a fuel option in these electrochemical systems. 30 combinations of 6 electrodes viz. Carbon (14 cm × 1.5 cm), Zn (14.9 cm × 4.9 cm), Cu (14.9 cm × 4.9 cm), Sn (14.1cm × 4.5cm), Fe (14cm × 4cm) and Al (14cm × 4.5 cm) were evaluated for each of the wastewater samples. Zn-C as anode-cathode combination produced a maximum voltage that was 1.084±0.016V and 1.086±0.028 and current of 1.777±0.115mA and 1.503±0.120 for KRM and SSR, respectively. In the present study, thick biofilm has been observed growing in MFC anode. Total 14 bacterial isolates growing in anode were obtained from two of the wastewater. The dual chambered, membrane-less and mediator-less MFCs were employed successfully to improve the economic feasibility of these electrochemical systems to generate bioelectricity and wastewater treatment simultaneously.Keywords: Membrane-less, Microbial Fuel Cells, Biofilm, Wastewater, Electrogenic.Article History: Received June 25th 2016; Received in revised form Dec 15th 2016; Accepted January 5th 2017; Available onlineHow to Cite This Article: Reena, M. and Jadhav, S. K. (2017) Bioelectricity production and Comparative Evaluation of Electrode Materials in Microbial Fuel Cells using Indigenous Anode-reducing Bacterial Community from Wastewater of Rice-based Industries. International Journal of Renewable Energy Develeopment, 6(1), 83-92.http://dx.doi.org/10.14710/ijred.6.1.83-92